2002
DOI: 10.1007/s00125-002-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of metformin into human milk

Abstract: The concentrations of metformin in breast milk were generally low and the mean infant exposure to the drug was only 0.28% of the weight-normalized maternal dose. As this is well below the 10% level of concern for breastfeeding, and because the infants were healthy, we conclude that metformin use by breastfeeding mothers is safe. Nevertheless, each decision to breastfeed should be made after conducting a risk:benefit analysis for each mother and her infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The mean infant exposure to drug ranged from 0.11% to 0.65% of the weight normalized maternal dose. [ 13 14 15 ] This is below the 10% level of concern for breastfeeding. In addition, the blood glucose concentrations in infants 4 hours after a feeding were within the normal limit.…”
Section: Introductionmentioning
confidence: 93%
“…The mean infant exposure to drug ranged from 0.11% to 0.65% of the weight normalized maternal dose. [ 13 14 15 ] This is below the 10% level of concern for breastfeeding. In addition, the blood glucose concentrations in infants 4 hours after a feeding were within the normal limit.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, metformin turned out to be safe in pregnant women with PCOS when treated to minimize intrapartum complications [91][92][93]. Metformin showed minimal excretion into the breast milk and no adverse effects on breastfed infants have been reported [94,95].…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…[ 26 ] As for the use of metformin small studies have shown that it is excreted in small amounts in breast milk. [ 27 28 ] The women should be counseled about the potential problems with the use of oral hypoglycemic agents during lactation and should preferably be put on insulin till they breastfeed the baby.…”
Section: A Fter D Ischargementioning
confidence: 99%